ANALYSIS OF THE HEALTH LEVEL OF BRI SHARIA BANK THROUGH RGEC METHOD FROM 2016 TO 2020 - Imam Ali Mustofa; Nurhayati Nurhayati; Fajruddin Fatwa; Muhammad Iqbal Surya Pratikto; Suqiyah Musyafa’ah (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2018)
With this research, it can be known whether or not BRI Syariah Bank is healthy through the application of the RGEC method from 2016 to 2020. In carrying out an analysis of the health of BRI Syariah banks, the author uses technical analysis of the data through the application of the RGEC method. This research uses a descriptive quantitative approach that uses the RGEC method or steps through 4 analysis components consisting of Risk Profile, GCG, Earnings, and Capital. Where the ratios contained in each component of the analysis are contained in a financial report. This study resulted in a conclusion that the soundness of BRI Syariah banks in 2016-2020 that applied the RGEC method assessed through four analysis components and eight ratios consisting of NPF, FDR, PDN, ROA, ROE, NI, BOPO, and CAR obtained a healthy rating.